Authors' Response. - Benefield, K. Elaine; Capie, William (Journal of Research in Science Teaching, 1977)
The article presents the author's response to the comments made on his study on the empirical deviations of hierarchies of propositions related to Piaget's binary operations. He stressed the significance of his study in obtaining a broad reflection of the sequence of development of specifically defined components of formal reasoning process. It is also assumed that the ordering by difficulty of propositional types is parallel to the ordering of the formal operations they were considered to represent. He also contended that he did intend to imply that competency with verbal representatives of any particular binary operation implied the subject had acquired formal thinking abilities in the Piagetian definition.